Environmental gestagens: Current insights on ecotoxicity and microbial transformations - Prasiddhi Parab; Sheena Kumari; Prashant Bhagwat; Santhosh Pillai (Environmental Chemistry and Ecotoxicology, 2025)
Environmental gestagens (EGs) consisting of both natural and synthetic progestins have emerged as a new class of micropollutants due to their widespread use by humans and in livestock for contraceptive and reproduction-related treatments. Consequently, their uncontrolled release into the environment has raised concerns due to their endocrine-disrupting activity, which can adversely impact the endocrine system functioning of vertebrates, even at concentrations as low as 1 ng/L. Despite extensive research on estrogenic and androgenic endocrine disruptors, the microbial degradation pathways of gestagens as well as their transformed metabolites, remain largely unexplored, representing a significant knowledge gap in environmental biotechnology. To address this void, we review the occurrence, fate, and ecotoxicity of EGs across various environmental matrices, with an emphasis on the critical role of microbiomes in their biodegradation. The presence and biotransformation of EGs in various environmental sources, including wastewater treatment plants, surface and marine waters, soil, and manure, are discussed, along with their intermediate metabolites. While previous reviews have widely covered microbial degradation of estrogenic compounds and androgenic pollutants, no comprehensive review has systematically examined the biodegradation pathways specific to gestagens. This review addresses this critical gap by being the first to comprehensively discuss the degradation and biotransformation pathways as well as the natural diversity of microorganisms capable of degrading EGs, revealing distinct microbial contributions that differ significantly from those involved in estrogen and androgen metabolism. Understanding the microbial degradation mechanisms of EGs and the metabolites produced can aid in selecting suitable hosts for bioremediation that possess the necessary catalytic capabilities. This will help to reduce the formation of toxic byproducts, thereby preventing secondary pollution. This gestagen-specific microbial degradation mechanism advances the field beyond the current understanding, which is limited to other steroid hormone classes. Additionally, this knowledge can be utilised to formulate microbial consortia for synergistic degradation of EGs, ultimately enhancing removal efficiency in environmental bioremediation applications.